Cocrystals of bis(hexamethylbenzene)iron hexafluorophosphate and tetrafluoroborate with arenes: A structural study. (1st August 2022) - Bezpalko, Mark W.; Lorson, Logan C.; Thomas, Christine M.; Foxman, Bruce M.
Graphical abstract: Structural studies of hexafluorophosphate and tetrafluroborate salts of the bis(hexamethyl-benzene)iron dication [(HMB)2 Fe] 2+ show a surprisingly wide variety of different stoichiometries and packing arrangements not anticipated in previous studies. In the cocrystal of ferrocene:[Fe(HMB)2 ][BF4 ]2 we observed an unexpected near-perpendicular orientation instead of the heterosoric parallel stacking more commonly observed. Abstract: The synthesis of a wide variety of electron-rich arene cocrystals containing CT interactions with salts of the bis(hexamethylbenzene)iron dication [(HMB)2 Fe] 2+ is reported; the hexafluorophosphate (1-P ) and tetrafluoroborate (1-B ) salts were used. The cocrystals led to a surprisingly wide variety of different stoichiometries and packing arrangements that were not anticipated in previous studies by Braitsch and Kochi. Specifically, in the cocrystal of ferrocene:[Fe(HMB)2 ][BF4 ]2 we observed a near-perpendicular orientation instead of heterosoric parallel stacking in other materials previously observed by Kochi. Nonetheless, we did observe heterosoric stacking in the majority of the cocrystals where the [(HMB)2 Fe] 2+ cation acts as an effective electron acceptor with a selected variety of electron-rich arene donors. Not surprisingly, when tetrachloro-1, 4-benzoquinone, a well-known electron acceptor was incorporated, we observed that the tetrachloro-1, 4-benzoquinone had no significant interactions with the [(HMB)2 Fe] 2+ cation. In addition we observed that a change of anion often generates interesting structural differences. The crystal structure of the diphenylamine cocrystal with 1-P displayed near-parallel heterosoric stacking, whereas the structure of the cocrystal with 1-B showed distorted heterosoric stacking. Cocrystals of the anthracene cocrystal with 1-P contain a 1:1 ratio of anthracene to 1-P, whereas those with 1-B are solvent-free and contain a 2:1 ratio of anthracene to 1-B . In addition, the naphthalene structures differ in stacking, with heterosoric parallel stacking observed in in the cocrystal of naphthalene with 1-P, while an alternating CH to π stacking orientation is observed in cocrystals of naphthalene with 1-B, and of cocrystals of mesitylene with 1-P . The present work demonstrates that the crystal structures, and indeed the crystal stoichiometries of the materials studied are not predictable. Ultimately each structure arises from a delicate interplay of the effects of putative donor-acceptor interactions, solvent incorporation (if any), cation-anion packing, and weak hydrogen bonding.